Matrices y marcos: dos figuras del funcionamiento de las normas en la obra de Judith Butler - Canseco, Alberto (2018)
“Matrixes and Frames: Two Figures of Norm Functioning in the Work of Judith Butler”. The concepts of “intelligibility matrix” and “frame”, each corresponding to different periods in the thought of the feminist philosopher Judith Butler, seem to converge in so many aspects that one is tempted to hold that they may be used indistinctly. Nevertheless, the problem this paper deals with is the possible uniqueness the usage of the latter concept involves, thus pointing to the differences between both concepts. I aim to solve the problem by studying the main sources that Butler herself uses in order to formulate the concept of frame, and by putting in evidence that which is gained by the use of that notion. I also aim to show more clearly the difference between the two concepts by appealing to their functions in the critique of speciffical cultural phenomenon: pornography as a frame and element of the heterosexual matrix.